Bioactivity of Cassia auriculata Methanol Extract against Human Pathogenic Bacteria and Fungi - Senthilkumar, P.K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Infectious disease can become a threat to public health in this world. The use of medicinal plants for the treatment of various diseases is an old practice in most countries and it still offers an enormous potential source of new anti-infective agents. The present study was conducted to evaluate the bioactivity of Cassia auriculata methanol extract against human pathogenic bacteria and fungi. The plant material was collected, shade dried and powdered. The powdered material was extracted using the organic solvent methanol. Antimicrobial activity of Cassia auriculata methanol extract was determined by Disc diffusion method. The zone of inhibition of Cassia auriculata methanol extract against bacteria was maximum against Vibrio cholerae followed by Klebsiella pneumoniae, Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa and Escherichia coli. The least zone of inhibition was recorded against Salmonella typhi. The Minimum Inhibitory Concentration (MIC) was ranged from 2mg/ml to 4mg/ml. The Minimum Bactericidal Concentration (MBC) value ranged between 2mg/ml and 4mg/ml. For fungi, the zone of inhibition was maximum against Candida albicans, followed by Aspergillus fumigatus, Aspergillus flavus, Aspergillus niger, Candida tropicalis and Candida cruzei. The least zone of inhibition was recorded against Penicillium sp. The MIC was 0.5mg/ml and the MFC value was 1mg/ml.